Pengembangan Lembar Kerja Peserta Didik (LKPD) Berbasis Discovery Learning Untuk Melihat Kemampuan Pemecahan Masalah Siswa SMP: Pengembangan LKPD - Silvia Rinjani Silvia; Sujinal Arifin; Feli Ramury (Faculty of Education and Teacher Training, State Islamic University of Sulthan Thaha Saifuddin Jambi, 2023)
This study aims to produce student worksheets (LKPD) based on discovery learning for class VIII students on relations and functions that have valid, practical qualities, and have a potential effect on students' problem-solving abilities. The research method used is the method of research and development (research and development). Field test subjects in this study were class VIII students of SMP Nurul Amal Palembang. This study uses the ADDIE development model, namely analize, design, develop, implement, and evaluate. The research data was obtained through observation, validation sheets, questionnaires, and tests of students' problem solving abilities. The results of this study are: 1) Mathematics worksheets with discovery learning models on relations and function materials have valid, practical, and potential effects on the results of students' problem solving abilities. valid” and material experts by 84% with the criteria of “very valid” so that the LKPD is declared valid; 3) Assessment of LKPD for practicality criteria obtains a percentage of 85% with the criteria of